Menggagas Fikih Tasamuh di Tengah Masyarakat Multikultural - Ridwan, Ridwan (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
An accommodative Islamic law is needed in this multicultural society. Ijtihad is an inner dynamic which guides the changes. Fiqh as the reflection of ulama responds the pluralism towards the problems in the society.